16S rDNA Full-Length Assembly Sequencing Technology Analysis of Intestinal Microbiome in Polycystic Ovary Syndrome - Dong, Sitong; jiao, Jiao; Jia, Shuangshuo; Li, Gaoyu; Zhang, Wei; Yang, Kai; Wang, Zhen; Liu, Chao; Li, Da; Wang, Xiuxia (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: To study the characteristics and relationship of the gut microbiota in patients with polycystic ovary syndrome (PCOS). Method: We recruited 45 patients with PCOS and 37 healthy women from the Reproductive Department of Shengjing Hospital. We recorded their clinical indexes, and sequenced their fecal samples by 16S rDNA full-length assembly sequencing technology (16S-FAST). Result: We found decreased α diversity and different abundances of a series of microbial species in patients with PCOS compared to healthy controls. We found LH and AMH were significantly increased in PCOS with Prevotella enterotype when compared to control women with Prevotella enterotype, while glucose and lipid metabolism level remained no significant difference, and situations were opposite in PCOS and control women with Bacteroides enterotype. Ruminococcus gnavus, Prevotella stercorea, Dialister succinatiphilus and Bacteroides fragilis were more abundant while Christensenellaceae spp. were less abundant in the PCOS group. P. stercorea was significantly more prevalent in PCOS-not insulin resistance (NIR) compared to control-NIR and PCOS-not overweight (NOW) patient groups compared to control-NOW groups. Kyoto Encyclopedia Genes and Genomes reflecting pathways related to lipopolysaccharide biosynthesis were more abundant in the PCOS group. Conclusion: Our study found gut microbiota that had different abundance in patients with PCOS compared to healthy controls. An intimate relationship was shown between the gut microbiota and pathological changes in PCOS. We suggest the gut microbiota should be taken into consideration in the treatment of symptoms of PCOS via drugs and diet.